The sorting of female careers after first birth: A competing risks analysis of maternity leave duration - Melanie Arntz; Stephan Dlugosz; Ralf A. Wilke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
A number of contributions have found evidence for motherhood being a critical life event for women's employment careers. This study presents a detailed model for the du- ration of maternity leave in which young mothers can make a transition into a number of states related to employment and unemployment among others. The model incorporates a large number of factors including the legal framework, individual and firm character- istics. We provide a comprehensive picture of the sorting mechanisms that lead to the differentiation of women's employment careers after birth. Our empirical evidence is de- rived from large linked administrative individual labour market data from Germany for a period of three decades. We obtain unprecedented insights how women's skills, the quality of the previous job match, firm level characteristics, labour market conditions and leave legislation are related to the length of maternity duration.
Keywords: J13; J18; C41; 330; work interruptions; cumulative incidence; leave legislation